2019
DOI: 10.1590/2179-8087.031116
|View full text |Cite
|
Sign up to set email alerts
|

Lumber Yield of Four Native Forest Species of the Amazon Region

Abstract: The objective of this study was to evaluate the volumetric lumber yield of four native species of the Amazon Region: Cedrinho (Erisma uncinatum Warm), Cumaru (Dipteryx odorata Aublet), Garapeira (Apuleia leiocarpa Voguel), and Cambará (Qualea paraensis Ducke). Twelve logs of each species with different diameters were randomly selected from different sawmills in northern Mato Grosso state, Brazil. Additionally, the influence of diameter on the yield of each species was evaluated through regression analysis. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…3f and 3b). The values found for this species were similar to those found by Lima et al (2020) and higher than those found by Melo et al (2019).…”
Section: Discussionsupporting
confidence: 89%
“…3f and 3b). The values found for this species were similar to those found by Lima et al (2020) and higher than those found by Melo et al (2019).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the volume yield is affected by different parameters, of which some are manageable, such as the log dimensions, while others, unfortunately, are nonavoidable, such as the defects and cracks. For example, the logs of the same diameter class may give yield values characterized by a low variation [3,11,40], especially in small sawmills where the machine operator manually chooses the dimensions of the sawn wood and the sawing pattern. To confirm the influence on the variation in performance in our study, Helvoigt and Adams [41] reported similar statistically significant relationships between sawlogs and sawn wood when analyzing the productivity by a 30-year study period in the Pacific Northwest sawmill industry.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the existence of a diversity of factors that can influence yield , the effect of conicity was demonstrated in this study, especially due to the care that was taken to homogenize the sample in terms of length, absence of hollows, final sawn products, besides the effort taken to not influence the decisions of the saw operator. It is important to emphasize that the diameter of the logs can also influence yield for certain species (Biasi and Rocha, 2007;Melo et al, 2019). However, there was no observed pattern of increase or decrease in yield with reduction of diameter from the base to the top of the stem, indicating that conicity probably had a greater influence.…”
Section: Conicity and Yield By Speciesmentioning
confidence: 94%
“…The conventional method of log sawing, in which the saw operator determines how the cuts will be made, still predominates in the Amazon region (Melo et al, 2019). In most cases the decision is random, and this will rarely result in a high level of yield (Biasi and Rocha, 2007).…”
Section: Introductionmentioning
confidence: 99%